Comparison of apnoea–hypopnoea index and oxygen desaturation index when identifying obstructive sleep apnoea using type‐4 sleep studies. (18th December 2018) - Senaratna, Chamara V.; Lowe, Adrian; Perret, Jennifer L.; Lodge, Caroline; Bowatte, Gayan; Abramson, Michael J.; Thompson, Bruce R.; Hamilton, Garun; Dharmage, Shyamali C.
Summary: The concordance of different indices from type‐4 sleep studies in diagnosing and categorising the severity of obstructive sleep apnoea is not known. This is a critical gap as type‐4 sleep studies are used to diagnose obstructive sleep apnoea in some settings. Therefore, we aimed to determine the concordance between flow‐based apnoea–hypopnoea index (AHIflow50% ) and oxygen desaturation index (ODI3% ) by measuring them concurrently. Using a random sub‐sample of 296 from a population‐based cohort who underwent two‐channel type‐4 sleep studies, we assessed the concordance between AHIflow50% and ODI3% . We compared the prevalence of obstructive sleep apnoea of various severities as identified by the two methods, and determined their concordance using coefficient Kappa(κ). Participants were aged (mean ± SD) 53 ± 0.9 years (48% male). The body mass index was 28.8 ± 5.2 kg m −2 and neck circumference was 37.4 ± 3.9 cm. The median AHIflow50% was 5 (inter‐quartile range 2, 10) and median ODI3% was 9 (inter‐quartile range 4, 15). The obstructive sleep apnoea prevalence reported using AHIflow50% was significantly lower than that reported using ODI3% at all severity thresholds. Although 90% of those with moderate–severe obstructive sleep apnoea classified using AHIflow50% were identified by using ODI3%, only 46% of those with moderate–severe obstructive sleep apnoea classified using ODI3% were identified by AHIflow50% . The overall concordance between AHIflow50% and ODI3% in diagnosing and classifying the severity of obstructive sleep apnoea was only fair (κ = 0.32), better for males (κ = 0.42 [95% confidence interval 0.32–0.57] versus 0.22 [95% confidence interval 0.09–0.31]), and lowest for those with a body mass index ≥ 35 (κ = 0.11). In conclusion, ODI3% and AHIflow50% from type‐4 sleep studies are at least moderately discordant. Until further evidence is available, the use of ODI3% as the measure of choice for type‐4 sleep studies is recommended cautiously.